Exploring the Influence of Determinants on Behavior Intention to Use of Multiple Media Kiosks Through Technology Readiness and Acceptance Model - Peng, Michael Yao-Ping; Yan, Xin (Frontiers in Psychology, 2022)
The use of multiple media kiosks (MMKs) is witnessing an increasingly strong uptrend in 24-hour chain convenient stores in developed countries. However, as the functions of MMKs intensifies and increases, how to retain consumers has been a topic that raises concerns of managers and researchers. In this study, we adopt the integrated technology acceptance model, which combines technology readiness and acceptance model with interactivity that serves as the moderating factor, with the purpose of discussing the relationships among all these variables and their impacts on behaviour intention to use. Through the cross-sectional survey and purposive sampling, a total of 623 copies of questionnaire from Taiwan were collected in this study. Smart-PLS for PLS-SEM was applied in the structural model to conduct a verification of the hypotheses and comparative analysis in this study. The results show that all hypotheses were significantly supported; technology readiness has a positive impact on perceived ease to use and perceived usefulness; and interactivity also positively moderates the relationship among perceived ease to use, perceived usefulness and attitude toward using. Our results will offer more insights and advice concerning theories of service technology.